Polyoma genome in hamster BHK-21-C13 cells: integration into cellular DNA and induction of the viral replication. - Folk, W R (1976)
When grown at 39.5 degrees C, BHK-21 C-13 cells transformed by A gene mutants of polyoma virus contain viral sequences that are predominantly associated with cellular DNA pelleted in the Hirt lysis procedure. At this temperature, in cells that are inducible for viral DNA replication (Folk, 1973), the majority of the viral genomes are covalently joined with cellular DNA's containing repetitious sequences. Upon a shift to 31 degrees C, free viral genomes appear and are replicated. Coupled with the replication of the free viral genomes at 31 degrees C is an increase in the viral genomes associated with cellular DNA.